PENGARUH RETURN ON EQUITY (ROE) DAN NET PROFIT MARGIN (NPM) TERHADAP LABA USAHA PADA BANK MILIK NEGARA SELAMA PERIODE 2011 - 2015 - Ariyanto Ariyanto; Muhammad Alhudhori; Sakinah Sakinah (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2017)
Profitability Ratio Has An Influence On Operating Profit, One Of Which Is Return On Equity (ROE) and Net Profit Margin (NPM). the company will be healthy and can improve Profits, if the company can earn an operating profit greater than the operational costs to be paid, so the Company Will Getting a bigger profit. Return On Equity (ROE) is the ratio to measure the ability to manage existing bank capital management to obtain a net profit. Profit Margin (NPM) ratio of net to measure the bank's ability to generate net profit from operating activities substantially. operating income is income derived solely from the main activity of the company or the difference between costs and gross operating profit.The data used in this research is secondary data obtained from financial statistics economic statistics Indonesia and Bank Indonesia from 2011 to 2015. Data analyzed using multiple linear regression analysis test. Analysis shows that the coefficient of determination R square was obtained for 0991. This result means that 99.1% Operating profit influenced Return On Equity (ROE) while the remaining 0.9% is influenced by other variables not examined in this study. Broadly speaking, the Return On Equity (ROE) Significantly Affect operatinincome. While the Net Profit Margin (NPM) has no effect on operating income.Keyword: return on equity, net profit margin